Tanggung Jawab Penanggung Dalam Asuransi Tanggung Jawab Hukum - Aulia Falillah; Yulius Rico Adrianto; Puti Anisa Erwan; Azlan Fahrezi; Yolan Dwi Putra, Helfira Citra (CV. ITTC INDONESIA, 2024)
Every human being does not rule out the possibility of facing risks due to his actions. This risk can come from agreements and laws and regulations that cause losses to victims, so they must be held accountable for their legal actions. Therefore, to avoid the risk of greater loss, a person can apply for self-insurance, remembering that the purpose of insurance is to transfer risk from the insured to the insurer. The formulation of the research problem is what is the responsibility of the insurer in legal liability insurance? This research uses a normative method with a statutory and conceptual approach, as well as secondary data in the form of primary legal materials and secondary legal materials with a conceptual analysis approach presented in the form of analytical descriptive narratives. One type of insurance, namely legal liability insurance, aims to transfer risk from the insured to the insurer regarding the insured's legal actions that cause losses to the victim. Legal actions can take the form of unlawful acts and breaches of contract. If you already have legal liability insurance and at a later date the insured commits a legal act that causes harm to the victim, then the insured's responsibility to provide compensation to the victim becomes the responsibility of the insurer. The form of responsibility is that the insurance company will provide compensation to the victim. Therefore, legal liability insurance is considered important now and in the future, to overcome the risk of legal actions that are very likely to occur.